Spray‐Coated Polymer Solar Cells based on Low‐Band‐Gap Donors Processed with ortho‐Xylene. Issue 9 (2nd September 2014) - La Notte, Luca; Polino, Giuseppina; Ciceroni, Claudio; Brunetti, Francesca; Brown, Thomas M.; Di Carlo, Aldo; Reale, Andrea
Abstract The use of low‐band‐gap polymer donors in the field of polymer solar cells (PSCs) allows to reduce the gap with other consolidated photovoltaic technologies because high conversion efficiencies can be achieved. Unfortunately, optimal performance is strongly correlated to the use of chlorinated solvents, known to be harmful in working conditions due to their toxicity towards environment and human health. For this reason, high‐performing PSCs have been deposited via small‐area techniques. We report on the use of a PBDTTT‐C‐T:PC70BM blend dissolved in the non‐chlorinated solvent ortho‐xylene for the deposition of spin‐coated and spray‐coated active layers in direct PSCs. An impressive conversion efficiency of 8 % is obtained for the spin‐coated blend, whereas the significant value of 4.4 % is achieved by using the spray‐coated blend. The work opens the way to the use of low‐band‐gap materials in spray coating, a non‐wasteful technique compatible with coating large areas.